Availability, prices and affordability of UN commissions life saving medicines for reproductive and maternal health in Uganda - Kibira, Denis; Kitutu, Freddy Eric; Merrett, Gemma Buckland; Mantel-Teeuwisse, Aukje K. (Journal of Pharmaceutical Policy and Practice, 2017)
Uganda was one of seven countries in which the United Nations Commission on Life Saving Commodities (UNCoLSC) initiative was implemented starting from 2013. A nationwide survey was conducted in 2015 to determine availability, prices and affordability of essential UNCoLSC maternal and reproductive health (MRH) commodities. The survey at health facilities in Uganda was conducted using an adapted version of the standardized methodology co-developed by World Health Organisation (WHO) and Health Action International (HAI). In this study, six maternal and reproductive health commodities, that were part of the UNCoLSC initiative, were studied in the public, private and mission health sectors. Median price ratios were calculated with Management Sciences for Health International Drug Price Indicator prices as reference. Maternal and reproductive health commodity stocks were reviewed from stock cards for their availability for a period of 6 months preceding the survey. Affordability was measured using wages of the lowest paid government worker.
Keywords: Prices and affordability; UN commissions life saving medicines; Reproductive and maternal health; Uganda